A study on critical dislocation of gasket for segmental linings of shield tunnels - Xuan Guo; Zhitong Li; Senyang Yuan (Scientific Reports)
Abstract Dislocation of segments in shield tunnels significantly contributes to joint leakage, making it crucial to identify the critical dislocation amount of segment linings. To explore the waterproofing mechanism of sealing gaskets under water pressure, a structural coupling finite element analysis model was created. This model simulates water intrusion dynamics at segment joints, analyzing contact stress distribution and waterproof performance across various dislocation amounts. The comparison of finite element calculations with experimental data shows a positive correlation, although simulation results are slightly lower than experimental findings. The analysis demonstrates that lower effective contact stress due to dislocation increases leakage risk. In small deformation ranges, opposite segment constraints can enhance gasket contact, reducing leakage risks. However, exceeding critical dislocation leads to leakage. Findings indicate that as dislocation increases, the effective contact stress between the gasket and groove first decreases, then increases. A dislocation of 9 mm and an opening of 8 mm yield the lowest effective contact stress proportion and worst waterproof performance, marking a critical point for sealing water pressure changes. This study provides a scientific basis for determining critical dislocation amounts, optimizing joint sealing performance, and reducing leakage in shield tunnels.